Novel organo-modifier for thermally-stable polymer-layered silicate nanocomposites. (December 2015) - Dintcheva, N.Tz.; Al-Malaika, S.; Morici, E.
Abstract: A new novel approach for the stabilisation of polymer-clay nanocomposites has been investigated based on reacting chemically an antioxidant function, a hindered phenol moiety, with an organic modifier based on a quaternary ammonium salt. The chemically linked antioxidant-containing organic modifier (AO-OM ) was then introduced into natural montmorillonite (MMt) through a cation-exchange reaction resulting in antioxidant-containing organo-modified clay (AO-OM-MMt ). The new antioxidant-containing modified clay, along with other organo-modified clays having a similar organo-modifier but without the reacted antioxidant, were characterised by spectroscopic, thermogravimetric and x-ray diffraction techniques and tested for their thermo-oxidative stability. PA11-based clay nanocomposites samples containing the AO-OM-MMt and the other organo-modified clays, both without and with an added (i.e. not chemically reacted) hindered phenol antioxidant (similar to the one used in the AO-OM) were prepared by melt processing and examined for their processing and long-term thermal-oxidative stability at high temperatures. It was shown that although the new organo-modifier, AO-OM, was also susceptible to the Hoffman elimination reaction, the nanocomposites containing this newly modified clay (PA11/AO-OM-MMt) showed higher melt processing and long-term thermo-oxidative stability, along with excellent clay dispersion and exfoliation, compared to the other PA11-nanocomposites examined here (with and without the conventionally added antioxidant). It is suggested here that the excellent overall performance observed for the PA11/AO-OM-MMt nanocomposites is due to an in-situ partial release of low molecular weight antioxidant species having stabilising functionalities that are capable of acting locally at the interface between the inorganic clay platelets and the polymeric matrix which is a critical area for the onset of degradation processes.